Optimization of hot air drying technology for bamboo shoots by response surface methodology - CAI, Qingfeng; LI, Zichun; GENG, Wenguang; LIU, Fang; YUAN, Dongling; SUN, Rongfeng; JIA, Binguang (Food Science and Technology, 2023)
The drying characteristics of bamboo shoot slices were experimentally studied in a hot air drying system. The individual and combined influence of air temperature, velocity, and slice thickness on the drying process was analyzed. The chromatic aberration and rehydration ratio were used as response indicators, and a 17-group experimental optimization of the drying process was carried out using a response surface methodology. According to the optimization analysis, a hot air temperature of 60.4 °C, an air velocity of 0.4 m/s, and a slice thickness of 0.2 cm were the optimal conditions for hot air drying of bamboo shoots. The predicted rehydration ratio and chromatic aberration of the dried bamboo shoot slices were 10.46 and 12.03, respectively. A validation experiment was conducted under optimum conditions to confirm the applicability of the models.